Outstanding Scientist, Breeder, Organizer of Colored Karakul Cultivation (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Today, it is necessary to breed Karakul sheep, improve their breed, and increase their productivity. It is no secret that sheep of this breed are a national selection, adapted to the climate and nature of Central Asia. In addition, it is one of the main branches of pasture livestock in our Republic. A number of products can be obtained from one sheep of this breed: fur, skin, meat and offal. Based on the requirements of the world market, it is possible to increase the level of obtained fur by 15-20%..